Pengaruh E-service Quality dan Net Oriented Lifestyle terhadap E-satisfaction dan E-loyalty (Studi pada Pelanggan E-ticketing di Kota Balikpapan) - Hendika S.L.; M.S. Idrus; Surachman -; Agus Suman (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
This study aims at examining the relationship between e-Service Quality and Net Oriented Lifestyle, and their influences toward e-Satisfaction and e-Loyalty in airlines e-ticketing setting context. In addition, the contribution of six dimensions involving usability, information quality, navigation, enjoyment, process, and privacy toward e-Service Quality is investigated as well.The empirical data were collected from 195 respondens with Net Oriented Lifestyle through their opinions about airlines e-ticketing experience. The findings of this study through Structural Equation Modeling analysis, indicate that: (1) the contribution of six dimensions covering usability, information quality, navigation, enjoyment, process, and privacy toward e-Service Quality is positive and very significant, (2) the correlation or the relationship of e-Service Quality and Net Oriented Lifestyle is positive and very significant, (3) the influence of e-Service Quality toward e-Satisfaction is positive and very significant, (4) the influence of e-Service Quality toward e-Loyalty is positive and significant, (5) the influence of Net Oriented Lifestyle toward e-Satisfaction is positive and very significant, (6) the influence of Net Oriented Lifestyle toward e-Loyalty is positive and significant, and (7) the influence of e-Satisfaction toward e-Loyalty is positive and very significant. Finally, concluded that all hypothesis of this study are scientifically confirmed.Keywords: e-Service Quality, Net-Oriented Lifestyle, e-Satisfaction, and e-Loyalty.